Evidence of Seismic-Related Liquefaction Processes within the Volcanic Record of the Campi Flegrei Caldera (Italy) - Stefano Vitale; Jacopo Natale; Roberto Isaia; Francesco D’Assisi Tramparulo; Sabatino Ciarcia (Geosciences, 2022)
We report the occurrence of several sand liquefaction structures, such as sand dikes, in the stratigraphic record of the Campi Flegrei volcano, located both inside and outside the caldera. Five sites were analyzed within the caldera and two outside. The grain size analysis of the sand fillings indicates that these deposits are very fine-to-coarse sands generally poorly sorted. All of the granulometry curves fall within the field of the liquefiable, loose sediments. Frequently, dikes are characterized by two fillings: a rim showing poorly sorted finer sands and a core with extremely poorly sorted coarser sediments. We suggest that seismic-related liquefaction processes triggered the injection of these sand dikes during unrest episodes in the last 15 kyr. In particular, the sand dikes located outside the caldera, characterized by larger thicknesses and lengths, mark an important extensional episode, probably associated with the caldera formation during the Neapolitan Yellow Tuff eruption at 15 ka. Furthermore, liquefaction structures within the caldera are related to the seismic activity, probably occurring during the Agnano–Monte Spina caldera formation and the volcano-tectonic ground deformation, predating Epoch 3b (4.3 ka) and the Monte Nuovo (1538 CE) eruptions. This study highlights that these seismic-related liquefaction structures are common within the volcanic record of the Campi Flegrei, suggesting that the sand source can be both the widespread marine succession underlying the Epoch 3 deposits in the caldera central sector and the primary ash layers extensively present in the volcanic record.